Frequency of Y chromosome Microdeletions in Turkish Infertile Men: Single Center Experience - Aysel Kalaycı Yiğin; Mehmet Seven; Deniz Ağırbaşlı; Gizem Erdoğan Erdur (Genel Tıp Dergisi)
Objective: Infertility is defined as the failure to achieve a clinical pregnancy after twelve months of regular unprotected sexual intercourse. Both genetic and environmental factors affect infertility. The aim of the study is to establish the frequency of the Y chromosome microdeletions in Turkish infertile men who were referred to our center (2016-2020) with severe oligozoospermia and azoospermia. Methods: A retrospective chart review study on patients who referred to our center between 2016-2020 due to infertility were included in the study. We evaluated microdeletions of the Y-chromosome STS markers AZFa, AZFb and AZFc, ZFX/ZFY, and terminal sY160 regions. Y-chromosome STS markers were evaluated by DNA fragment analysis. Results: The chart review indicated that a total of 319 men applied to our genetic diagnosis center between 2016 and 2020 due to infertility (mean age 32 ±7). Among the 319 infertile men, we determined 21 cases with Y chromosome microdeletions (6.89%), with the most common AZFc deletion (n=11, 52.3%) which is consistent with literature. Conclusion: Y-microdeletions are among the most common genetic causes of male infertility. In azoospermic and oligospermic patients, cytogenetic tests, Y-chromosome microdeletions and NGS panel screening tests can give effective information before the use of assisted reproductive techniques.